PENGARUH TEKANAN WAKTU AUDIT DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT (Studi Pada Kantor Akuntan Publik di Bandung) - Anisa Shafa Aunur Rozana; Ery Yanto; Pandu Adi Cakranegara (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Auditors as one of the capital market supporting professions have an important role. Auditors provide opinions on financial statements which are then used by stakeholders to make decisions. Stakeholders will use the financial statements only if the financial statements can reflect the reasonable condition of the company. This is where the role of the auditor's opinion is to provide an opinion on the company's financial statements. In the process of giving an opinion, the auditor first conducts an audit of the company. When conducting an audit, the auditor is often faced with a limited audit time. This study examines how auditors can produce quality audits under time pressure while maintaining professionalism. The study was conducted at Public Accounting Firms in Bandung. From the results of the study it was found that limited time reduces audit quality, but auditors can still maintain audit quality by being professional.